The effect of regular aerobic activity on cortisol levels in female Wistar rats - Ibrahimaj Gashi, Arbnore; Azemi, Arjeta; Zivkovic, Vujica; Gontarev, Serjoza; Gjorgovski, Icko (Biomedical Research and Therapy, 2021)
Introduction: Physical inactivity has been identified as a major risk factor for global mortality, causing approximately 2 million deaths globally, whereas the physical activity of moderate intensity has significant benefits for health. Exposure to stress results in changes in the endocrine and autonomic nervous systems, as well as behavioral changes which allow an organism to adapt to environmental changes. This study aimed to assess changes in cortisol levels and body temperature in rats after forced swim tests. Methods: Female Wistar rats were divided into two groups: a control group (n = 10; not subjected to a forced swim test) and an experimental group (n = 10; subjected to a forced swim test). The forced swim test (60-90 min) was given to the experimental group for 21 days. Body temperature was measured rectally every day, and blood was taken from the animals on the 1st, 7th, 14th, and 21st days of the experiment to determine cortisol levels using a Mouse/Rat Cortisol ELISA protocol. Results: The results showed a statistically significant difference in the cortisol level between the groups on day 21 (p < 0.05). We found a significant reduction in the recurrent temperature after exposure to physical stress. Conclusions: Regular aerobic activity at a submaximal level for 21 days can reduce the hormonal stress response in female Wistar rats.